2023
DOI: 10.3389/fnut.2023.1075619
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index value in the prognosis of Kawasaki disease with coronary artery lesions

Abstract: ObjectivesThe prognostic nutritional index (PNI) is a purported predictor of intravenous immunoglobulin (IVIG) resistance and coronary artery aneurysm (CAA) development in patients with Kawasaki disease (KD). However, limited data exist on CAA regression. This study aimed to confirm whether the PNI is a predictor for CAA persistency in patients with KD.MethodsThis retrospective study grouped 341 patients with KD based on the coronary artery status and time of aneurysm persistence. The clinical and laboratory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…The study revealed an association between low pretreatment PNI levels and a high incidence of CAL as well as IVIG resistance in KD patients, which was consistent with a previous study (18). The key variation among these studies lies in the PNI cutoff values.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The study revealed an association between low pretreatment PNI levels and a high incidence of CAL as well as IVIG resistance in KD patients, which was consistent with a previous study (18). The key variation among these studies lies in the PNI cutoff values.…”
Section: Discussionsupporting
confidence: 89%
“…Over the past decades, malnutrition has garnered widespread attention as a prognostic indicator for various diseases, including acute myocardial infarction, heart failure, and various cancers (11, 26-30). Hence, some researchers have demonstrated that PNI may serve as a superior indicator for assessing the inflammatory and immune system status in KD patients (16,18,21). The PNI may provide early diagnosis and predictions for IVIG resistance in KD patients, as well as KD-CAL patients, thereby assisting in the timely implementation of appropriate treatment strategies for KD patients (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 Currently, the initial ratio of neutrophils to lymphocytes, γ-glutamyl transpeptidase, prognostic nutritional index (PNI), and CAA size are reported as risk factors for persistent CAAs. 22,23 However, the effect of concomitant infections was not considered in the above studies. In this study, we aimed to analyze the relationship between CAA formation and infections in patients with KD and further evaluate the relationship between concurrent infections and CAAs without recovery for a 2-year follow-up period.…”
Section: Introductionmentioning
confidence: 99%